SEGMENTING ONLINE SHOPPERS: A STUDY OF CONSUMERS' WEB PORTAL SELECTION MOTIVATIONS FOR E-SHOPPING - Sanjeev Prashar,; T. Sai Vijay, (Asian Academy of Management Journal, 2016)
As the internet permeates geographic boundaries and varied demographic strata, electronic commerce/online shopping is witnessing exponential growth. The objective of this research is to segment online shoppers based on attributes of web portals. A survey using a questionnaire was administered to 203 shoppers in India. Factor analysis is used to determine the factors that influence the selection of web portals. The robustness of the model developed using factor analysis was checked using Confirmatory Factor Analysis (CFA). Finally, cluster analysis was applied for identifying the clusters of respondents and profiling them. Based on cluster analysis, the study identified four segments: Traditional Shoppers, Benefit Seekers, Convenience and Assurance Seekers and Information and Price Seekers. Each of the four segments varies considerably in terms of their selection of website/portals for purchases, portraying the differences in their online shopping orientation. Against the general perception that shoppers prefer web portals that provide best user experience and attractive web atmospherics, this research shows that their inclination is towards brand image of the web portal and also being able to get value proposition through the website. Firms need to develop plans to consider the unique characteristics of the online market segments for an optimum allocation of marketing expenses. Findings of this research may be used as guidelines for the development of multi-dimensional strategic framework by online retailing firms.